2018
DOI: 10.1002/jcb.27431
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in breast cancers: Differences based on estrogen receptor status and recurrence

Abstract: DNA methylation plays a role in the etiology of primary breast cancers. We analyzed paired primary and second breast tumors to elucidate the role of methylation in recurrence. Methylation profiles from paired primary and second breast tumors of 23 women were assessed using the HumanMethylation450 BeadChip. Twelve women had estrogen receptor positive (ERpos) primary and second tumors, five had estrogen receptor negative (ERneg) primary and second tumors, and six had an ERpos primary tumor but an ERneg second tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…We observed a higher frequency of hypermethylated miRNA genes in ER-compared to ER + tumors from AA women, but a lower frequency of hypermethylation in ER-versus ER + tumors from EA women. Consistent with our ndings for tumors from EA women, several studies focused on DNA methylation of coding genes observed a higher frequency of hypermethylated genes in ER + tumors (8,31,32). One explanation for this may be that ER-related signaling molecules may enhance the activity of DNA methylation transferases to catalyze the transfer of a methyl group to a DNA segment, thus lead to the speci c gain of DNA methylation in ER + tumors.…”
Section: Discussionsupporting
confidence: 90%
“…We observed a higher frequency of hypermethylated miRNA genes in ER-compared to ER + tumors from AA women, but a lower frequency of hypermethylation in ER-versus ER + tumors from EA women. Consistent with our ndings for tumors from EA women, several studies focused on DNA methylation of coding genes observed a higher frequency of hypermethylated genes in ER + tumors (8,31,32). One explanation for this may be that ER-related signaling molecules may enhance the activity of DNA methylation transferases to catalyze the transfer of a methyl group to a DNA segment, thus lead to the speci c gain of DNA methylation in ER + tumors.…”
Section: Discussionsupporting
confidence: 90%
“…We observed a higher frequency of hypermethylated miRNA genes in ER-compared to ER+ tumors from AA women, but a lower frequency of hypermethylation in ER-versus ER+ tumors from EA women. Consistent with our findings for tumors from EA women, several studies focused on DNA methylation of coding genes observed a higher frequency of hypermethylated genes in ER+ tumors [8,30,31]. One explanation for this may be that ER-related signaling molecules may modify the activity of DNA methylation transferases that catalyze the transfer of a methyl group to a DNA segment and/or enzymes involved in demethylation of DNA (e.g., TET1-3, APOBEC), thus lead to the specific gain of DNA methylation in ER+ tumors.…”
Section: Plos Onesupporting
confidence: 92%
“…S4). DNA methylation has been implicated as a mechanism to silence ERα expression in ERα − BrC (24). Three CpG islands are predicted in the ERα promoter regions (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%